Enhancing Islamic Religious Education: Principles and Implications for Curriculum Development in the 2013 and Independent Curriculum Era - Mariani; Ahmad Fahrizal Akbar; Mim Fadhli Rabbi; Salamah (Presscience, 2024)
The curriculum is a fundamental component of education, serving as a framework to guide effective teaching and learning processes. To implement Islamic Religious Education (PAI) effectively and achieve its objectives, PAI teachers must possess a strong understanding of the principles underpinning PAI curriculum development. This study aims to explore the general principles of curriculum development, analyze specific principles related to PAI curriculum design, and examine their implications for the 2013 curriculum and the independent curriculum. Utilizing a literature review methodology, this study highlights that the principles of PAI curriculum development should align all learning activities with Islamic education while focusing on the students' potential, needs, character, and environmental context. Additionally, the curriculum must be diverse, integrated, responsive to rapid societal changes, relevant to societal and life needs, supportive of lifelong learning, and balanced between national and global interests. Furthermore, the principles of relevance, flexibility, continuity, efficiency, and effectiveness should be prioritized to ensure that curriculum development objectives are well-structured and achievable. The findings indicate that the principles of PAI curriculum development complement the 2013 curriculum and the independent curriculum, providing a cohesive framework for advancing Islamic education in contemporary contexts.